2006
DOI: 10.3406/intel.2006.1291
|View full text |Cite
|
Sign up to set email alerts
|

L’utilisation des textes procéduraux : lecture, compréhension et exécution d’instructions écrites

Abstract: L'utilisation des textes procéduraux : lecture, compréhension et exécution d'instructions écrites Laurent HEURLEY , Franck GANIER # RESUME. Le présent article expose les principaux modèles proposés en Psychologie cognitive pour décrire les processus cognitifs impliqués dans l'utilisation des textes procéduraux écrits (notices explicatives, modes d'emploi, etc.) et le traitement des instructions qui y figurent. Cette revue s'articule en deux parties. La première décrit brièvement les méthodes permettant d'étudi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 29 publications
(55 reference statements)
0
2
0
Order By: Relevance
“…Indeed, the work carried out over the last 40 years in the field of procedural learning (Ganier, 2013) shows that, in real-life situations, instructions consultation alternates with the execution of actions according to a phenomenon called action atomization (Vermersch, 1985). When no particular instruction is provided to the user about how to handle the assigned task, he or she will go through a succession of processing cycles during which reading activities of short text segments alternate with execution activities (Heurley & Ganier, 2006). In a study, Vermersch (1985) observed that individuals cut instructions into "elementary tasks" that each correspond to an action, or a part of action.…”
Section: The Action Atomization Phenomenonmentioning
confidence: 99%
“…Indeed, the work carried out over the last 40 years in the field of procedural learning (Ganier, 2013) shows that, in real-life situations, instructions consultation alternates with the execution of actions according to a phenomenon called action atomization (Vermersch, 1985). When no particular instruction is provided to the user about how to handle the assigned task, he or she will go through a succession of processing cycles during which reading activities of short text segments alternate with execution activities (Heurley & Ganier, 2006). In a study, Vermersch (1985) observed that individuals cut instructions into "elementary tasks" that each correspond to an action, or a part of action.…”
Section: The Action Atomization Phenomenonmentioning
confidence: 99%
“…For this reason, the relationship between a title's linguistic and semantic aspects and content complexity in RA texts have also been studied 4 . In addition, titles are relevant for the initial cognitive representation of the whole text they represent 1,12 while, at the same time, guiding its interpretation: they are, in other words, the criterion against which to measure the RA's degree of informativeness and relevance 13 .…”
mentioning
confidence: 99%